2015
DOI: 10.18632/oncotarget.3042
|View full text |Cite
|
Sign up to set email alerts
|

ERp57 modulates STAT3 activity in radioresistant laryngeal cancer cells and serves as a prognostic marker for laryngeal cancer

Abstract: Although targeting radioresistant tumor cells is essential for enhancing the efficacy of radiotherapy, the signals activated in resistant tumors are still unclear. This study shows that ERp57 contributes to radioresistance of laryngeal cancer by activating STAT3. Increased ERp57 was associated with the radioresistant phenotype of laryngeal cancer cells. Interestingly, increased interaction between ERp57 and STAT3 was observed in radioresistant cells, compared to the control cells. This physical complex is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 44 publications
(82 reference statements)
3
60
1
2
Order By: Relevance
“…These findings may be the supportive evidence that PDIA3 functions mainly through the STAT3 signaling pathway. These results are consistent with those from several cancer cell lines (18,19), suggesting that PDIA3 is involved in the phosphorylation process and the DNA-binding activity of STAT3. Furthermore, an association was observed between PDIA3 and P-STAT3 expression in HCC tissues.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings may be the supportive evidence that PDIA3 functions mainly through the STAT3 signaling pathway. These results are consistent with those from several cancer cell lines (18,19), suggesting that PDIA3 is involved in the phosphorylation process and the DNA-binding activity of STAT3. Furthermore, an association was observed between PDIA3 and P-STAT3 expression in HCC tissues.…”
Section: Discussionsupporting
confidence: 91%
“…In several types of cancer, PDIA3 forms a complex with STAT3 in the nucleus (16)(17)(18). A high frequency of PDIA3-STAT3 complex formation is a marker of poor prognosis and increases resistance to radiotherapy in laryngeal cancer through modulation of STAT3 activity (19). We have previously reported that the PDIA3 expression levels in HCC tissues are higher than those in adjacent non-cancerous tissues, and that they are associated with overall survival time (20).…”
Section: Downregulation Of Protein Disulfide-isomerase A3 Expression mentioning
confidence: 99%
“…28 Suppression of the ERp57-STAT3 pathway is necessary to enhance the efficacy of radiotherapy in human laryngeal cancer. 29 In lung adenocarcinoma study, we found that the levels of STAT3/p-STAT3 were higher in irradiation-induced A549/R34 cells than in A549 cells. Knockdown of STAT3 by miR-320a significantly increased the apoptosis of A549/R34 cells induced by irradiation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 77%
“…73 ERp57 is associated with tumor progression ans has been described to modulate STAT 3 activity, thus regulating radioresistance in laryngeal cancer. 74 Accordingly, ERp57 has been described as a poor prognosis factor.…”
Section: Dna Damage Repair Biomarkersmentioning
confidence: 99%